Strategi Pembelajaran Peningkatan Keterampilan Berpikir Melalui Pembelajaran PAK kepada Siswa Remaja - Mulus, Mulus; Tambunan, Ruhut Parningotan; Arifianto, Yonatan Alex (Sekolah Tinggi Teologi Baptis Indonesia, 2025)
The thinking ability of adolescent students is an important aspect of a meaningful and deep learning process. In the midst of challenging times, students are required not only to understand the material, but also to be able to think critically, logically, and reflectively. Unfortunately, the learning process in the classroom is often still teacher-centered and has not fully directed students to actively think independently. This phenomenon can be seen in the low ability of students to express opinions and analyze daily life problems from the perspective of the Christian faith. This research aims to develop an effective Christian Religious Education (PAK) learning strategy in improving the thinking skills of adolescent students through interactive, reflective, and contextual approaches. Using a descriptive qualitative research method using observation, interview, and documentation techniques on teachers and students, this study evaluates the effectiveness of learning strategies that encourage students' active participation in discussions and case studies to improve their understanding of Christian faith values as well as decision-making skills. The novelty of this research lies in the integration of learning methods that are oriented towards the development of critical and reflective thinking skills through an experiential approach and real-life case studies. This approach not only enriches students' understanding of the PAK material but also encourages them to connect Christian values with the challenges of everyday life more deeply. Thus, appropriately designed PAK learning strategies can be an effective means of building a critical, reflective, and responsible mindset.